Ensuring Liberties: Understanding State Restrictions on Religious Freedoms. Issue 4 (December 2014) - Finke, Roger; Martin, Robert R.
<x xml:space="preserve">Abstract</x> Promises of religious freedoms have become the standard in national constitutions. Yet, despite these assurances, religious freedoms are routinely denied. Combining new data collections with expanded theoretical explanations, this research explores how dimensions of governance and measures of the religious economy contribute to government restrictions on religion. Consistent with recent work on the judicialization of politics, we find that the absence of an independent judiciary is an important predictor of government restrictions on religious freedoms, whereas free elections and government effectiveness are insignificant in our full models. Consistent with the religious economy theory, we find that social restrictions and government favoritism toward a religion(s) are persistent predictors of the government's restrictions. Although the proportion of the population Muslim holds a strong bivariate association with government restrictions (r = .57), the relationship is reduced to insignificance in our full models. We briefly discuss the implications of these findings.